Stylistic analysis of the covers and facades in the domestic architecture - XIX & XX centuries - province of Chiclayo - Cosmópolis Bullón, Jorge (2021)
The history of domestic architecture in the city of Chiclayo is a pending undeveloped research topic, perhaps overshadowed by the abundance of information about our pre-Hispanic backgrounds. However, this architecture exists and we still have proof of it, unaltered, enduring the onslaught of modern edifications. Unfortunately, the ongoing prosperity misunderstands progress with destruction of history and culture, in the most thorough attempt to “eradicate idolatries”. For this reason and as a primary objective we have found it necessary to present an aspect of the image that characterized Chiclayo in the 19th century and its shift towards technologies and styles prevailing in the rest of the country: the facades to urban housing in the city of Chiclayo.